Belapeirez - Agirre, Pello (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1998)
Athanase Belapeire is the author of Catechima laburra (1696), one of the most important sources for the study of the Suletin dialect. He belonged to the prestigious Bela family, who were champions of Calvinism in the fighting that took place in Zuberoa during the XVIth century. His father, the famous Jacques de Bela, was a Protestant all through his life but Belapeire is already a catholic priest. As vicar general, Bishop of Oloron's delegate in Zuberoa, he worked for the Counter reform. Zuberoa belonged to the diocese of Oloron, but the conflict between vicar general Belapeire -who was supported by the Souletin priests and parishioners- and the bishop Salettes shows that the unity of the diocese is not a true one. Accordingly, Belapeire writes in Basque a catechism for the Basque part of the diocese and has it printed against the bishop's wishes. In 1706 the catechism by Joseph de Revol, written in French and translated to Basque and Bearnes, will be established for the whole diocese. Several of the Catechima laburra's sources have been identified: the second part, explaining religious festivities, is a translation of Bossuet's 1687 catechism and six paragraphs are taken from the Dotrina Christiana by Materre.